Processing Vegetable Waste оf Different Origin - Tkachenko, T.V.; Yevdokymenko, V.O.; Kamenskyh, D.S.; Filonenko, M.M.; Vakhrin, V.V.; Kashkovsky, V.I. (Science and Innovation, 2024)
Introduction. Biomass is primarily used as energy source, however, it is a valuable chemical raw material. As of today, there are about 20 basic compounds that are sufficient to provide a wide range of chemical products can be obtained from vegetable raw materials. Problem Statement. Despite a huge capacity of vegetable waste recycling for the industrial needs, so far research in this area has received a little attention in Ukraine. Purpose. To create an effective technological solution that ensures a comprehensive, waste-free processing of vegetable waste to produce marketable products. Materials and Methods. The methods of organic solvent pulping, explosion autohydrolysis, heterogeneous catalysis, and numerous analytical techniques (technical, elemental, structural analysis) have been used for the study. Results. The autohydrolysis treatment of plant material has been shown to enable destroying the original compact and strong structure into individual components. For microcrystalline cellulose (MCC), total conversion increases by 6-18% with a high crystallinity index (CI) of 0.81. As a result of alkaline treatment of rice husks, the inorganic component has been established to be "extracted" and to decrease in content. This is accompanied by partial delignification and a simultaneous increase in the content of cellulose. Using the method of organic solvent pulping of silica-free husk, the maximum amount of MCC (100% theoretically possible yield) with a CI of 0.77, a polymerization of 560.5, and a purity of 99.3% has been extracted. Silicon dioxide with a purity of, at least, 99.99% has been obtained. Conclusions. A way for obtaining cellulose from vegetable waste by the organic solvate pulping method has been described and the effect of pretreatment of lignocellulose biomass on the physical and chemical properties of obtained cellulose has been established.